A historical survey of the Corunca Castle, Romania, based on the military survey maps and present-day measurements - Kovács Lóránt (Acta Universitatis Sapientiae: Agriculture and Environment, 2015)
Corunca is situated at 4.5 km SE from Târgu-Mureș, near the Salt Stream, the Bozeni Stream, and the Vațman Stream. Its area is inhabited from ancient times. Both prehistoric and Roman findings were reported to have been found within the village boundaries. Its neighbouring medieval village, Sárvári, perished in the 16th century, while Kisernye was devastated by Turkish troops in 1661. The settlement was first recorded in 1332 as Korunka. The Reformed Church was built between 1769 and 1778, while its spire dates from 1793. The earlier church was surrended by high protective walls, which were demolished in 1769.